The Effect Of Hand Puppet As Media Towards Students’ Speaking Skills At Smkn 1 Bangkinang Kota - Gessica Fahmiranda; Masrul Masrul; Citra Ayu (Culture education and technology research (Cetera), 2024)
The aim of this research was to find out whether the using of hand puppets as a media has a significant effect on students’ speaking skills at tenth grade of SMKN 1 Bangkinang Kota. The method of this research used quasi-experimental with two group pre-test and post-test design. The population of the research was the tenth-grade students of SMKN 1 Bangkinang Kota in the academic year 2022-2023. The sample of this research was the MM class as an experimental class consisting of 35 students, and the RPL class as a control class consists 36. The data were collected by using a speaking test (pre-test and post-test). The result of the data analysis showed that there was a significant effect on the students’ speaking skills after being treated by using a hand puppet as a media for teaching speaking. It was verified by the value of sig. (2-tailed) was 0.000 < 0.05. As a consequence of the results, the null hypothesis (H0) was rejected and the alternative hypothesis (Ha) was accepted. It is possible to infer that the hand puppets approach has a considerable impact on students’ speaking skills.